MENINGKATKAN KETERAMPILAN SOSIAL ANAK USIA 3-4 TAHUN MELALUI METODE BERMAIN PERAN DI PPT TUNAS PRIMA KEBRAON SURABAYA - Andini Hardiningrum; Jauharotur Rihlah (MOTORIC, 2019)
Role playing methods are how to teach carried out by the teacher by imitating the behavior of a social situation. Role playing methods place more emphasis on participation in students to play roles / plays in terms of imitating social problems. Social skills is a skill capable of being seen in action, able to search, choose and manage information, able to learn new things that can solve everyday problems, able to have communication skills both oral and written, understanding, appreciating, and being able to work together with other people who are plural, capable of transforming academic abilities and adapting to the development of society. The purpose of this study was to determine the improvement of social skills through role playing methods in children aged 3-4 years at PPT Tunas Prima Kebraon Surabaya. The research design used was Classroom Action Research (CAR). The subjects of this study were children aged 3-4 years at PPT Tunas Prima Kebraon Surabaya. The results showed the average value of social skills before the application of the role playing method (prasiklus) 54.25% and the average value of social skills after the application of the role playing method (cycle II) 86.25%, thus obtaining an increase in social skills through playing methods the role is 32%. The conclusion of this study is that there is an increase in social skills through role playing methods in children aged 3-4 years at PPT Tunas Prima Kebaon Surabaya.